1998
DOI: 10.1006/dbio.1998.8911
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Patterns of Retinoic Acid Synthesis and Response in the Developing Mammalian Heart

Abstract: Retinoic acid (RA) has been implicated in cardiac morphogenesis by its teratogenic effects on the heart, although its role in normal cardiogenesis remains unknown. To define the parameters of RA action in cardiac morphogenesis, we analyzed the patterns of ligand synthesis, response, and inactivation in the developing mouse heart. Activation of a lacZ transgene controlled by an RA response element (RARE) was compared to the localization of the retinaldehyde-oxidizing dehydrogenase RALDH2, the earliest RA synthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
171
0
20

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 211 publications
(211 citation statements)
references
References 40 publications
20
171
0
20
Order By: Relevance
“…1E-G; see below for details). Altogether, RARE-hsp68-driven Cre excision is, therefore, consistent with the known pattern of activity of the RAREhsp68-lacZ transgene in the embryonic trunk, cervical, and rostral head regions (Rossant et al, 1991;Moss et al, 1998;Mic et al, 2002Mic et al, , 2004aRibes et al, 2006).…”
Section: Activation Of the Rare-cre Fate Markersupporting
confidence: 79%
See 1 more Smart Citation
“…1E-G; see below for details). Altogether, RARE-hsp68-driven Cre excision is, therefore, consistent with the known pattern of activity of the RAREhsp68-lacZ transgene in the embryonic trunk, cervical, and rostral head regions (Rossant et al, 1991;Moss et al, 1998;Mic et al, 2002Mic et al, , 2004aRibes et al, 2006).…”
Section: Activation Of the Rare-cre Fate Markersupporting
confidence: 79%
“…1D; details about the distribution of labeled cells are given in the next sections). Again, this spatial distribution strikingly mimics the pattern of activity of the RAREhsp68-lacZ transgene (Rossant et al, 1991;Moss et al, 1998;Ribes et al, 2009;Uehara et al, 2009;Supp. Fig .…”
Section: Activation Of the Rare-cre Fate Markermentioning
confidence: 58%
“…These first areas to become covered are the AV and conoventricular (CV) grooves resulting in the formation of a characteristic set of epicardial cuffs in these intersegmental areas. Subsequently, the epicardium spreads over the rest of the myocardial surface (Vrancken Peeters et al, 1995;Moss et al, 1998;Xavier-Neto et al, 2000).…”
Section: From Proepicardium To Epicardiummentioning
confidence: 99%
“…This is important since retinoic acid is known to be essential in cardiac development (Dyson et al, 1995;Gruber et al, 1996;Kastner et al, 1997;Niederreither et al, 2000;Chen et al, 2002;Stuckmann et al, 2003). Furthermore, it has been demonstrated that retinoic acid is actively synthesized by RALDH2 in the epicardiums of both mammals and avians (Moss et al, 1998;Xavier-Neto et al, 2000;Pérez-Pomares et al, 2002b). Thus the interaction between WT1 and RALDH2 likely plays a critical role in the differentiation of the EPDC.…”
Section: To Differentiate or Not To Differentiatementioning
confidence: 99%
“…Studies in chick and mouse have implicated retinoic acid (RA) signaling as a positive influence on atrial development (Yutzey et al, 1994;Moss et al, 1998;Fig. 3.…”
Section: Which Genes Establish the Ventricular And Atrial Lineages?mentioning
confidence: 99%